Gas Absorption by Alkaline Solution in a Cyclone Scrubber: Experimental and Modeling Study - Mariana, Mariana; Sumida, K.; Satake, T.; Maezawa, A.; Takeshita, T.; Uchida, S. (Jurnal Rekayasa Kimia & Lingkungan, 2009)
Experimental and modeling studies have been conducted on a CO2 absorption in a cyclone scrubber operated at room temperature. The effects of parameters such as the initial concentration of alkali in the solution and the liquid gas ratio on the CO2 absorbed flux were experimentally and theoretically investigated. A theoretical study has been performed using a mathematical model based on the absorption in the liquid droplet with instantaneous reaction, in the inlet duct of the cyclone and in the cyclone itself. The results from the model were compared with experimental data and showed satisfactory agreement. Keywords: CO2 removal, mathematical model, wet cyclone scrubber